"Pushing the Limits": Rethinking Motor and Cognitive Resources After a Highly Challenging Balance Training Program for Parkinson Disease. Issue 1 (11th August 2016) - Leavy, Breiffni; Roaldsen, Kirsti Skavberg; Nylund, Kamilla; Hagströmer, Maria; Franzén, Erika
Abstract: Background: There is growing evidence for the positive effects of exercise training programs on balance control in Parkinson disease (PD). To be effective, balance training needs to be specific, progressive, and highly challenging. Little evidence exists, however, for how people with PD-related balance impairments perceive highly challenging and progressive balance training programs with dual-task components. Objective: The purpose of this study was to explore and describe perceptions of a highly challenging balance training program among people with mild to moderate PD. Design: This study was qualitative in nature. In-depth interviews were conducted with 13 individuals with mild to moderate PD who had participated in a highly challenging balance training program. Interview transcripts were analyzed using qualitative content analysis, with an inductive approach. Results: The analysis revealed 3 subthemes concerning participants' perceptions of highly challenging and progressive balance training: (1) movement to counter the disease, (2) dual-task training in contrast to everyday strategies, and (3) the struggle to maintain positive effects. The first subtheme reflects how physical activity was used as a short-term and long-term strategy for counteracting PD symptoms and their progression. The second subtheme incorporates the described experiences of being maximally challenged in a secure and supportive group environment, circumstances that stood in contrast to participants' everyday lives. The third subtheme describes participants' long-term struggle to maintain program effects on cognitive and physical function in the face of disease progression. Interpretation of the underlying patterns of these subthemes resulted in one overarching theme: training at the limits of balance capacity causes a rethinking motor and cognitive resources. Limitations: The findings of this study cannot be considered to reflect the beliefs of those with weaker or negative beliefs concerning physical activity or be transferred to those at more severe stages of the disease. Conclusions: Findings from this study suggest that being pushed to the limits of balance capacity provoked people with mild to moderate PD to rethink their individual motor and cognitive resources, a process that was further enabled by the PD-specific group setting.